Toward Competitive Employment for Persons with Intellectual and Developmental Disabilities: What Progress Have We Made and Where Do We Need to Go. (September 2018) - Wehman, Paul; Taylor, Joshua; Brooke, Valerie; Avellone, Lauren; Whittenburg, Holly; Ham, Whitney; Brooke, Alissa Molinelli; Carr, Staci
Progress toward competitive integrated employment (CIE) for people with intellectual and developmental disabilities (IDD) over the last 40 years has been mixed. Despite evidence showing that supported employment interventions can enable adults with IDD to effectively get and keep jobs, national rates of integrated employment remain below a third of the working-age population. Progress is being made to improve these outcomes. Pathways have been identified that lead to CIE through supported employment, customized employment, internship experiences, and postsecondary education. The recent passage of the Workforce Innovation and Opportunity Act (WIOA) has created fresh momentum and increased the onus on interagency collaboration. This article examines what is known about promoting CIE through these pathways and highlights recommendations for future research and policy change. Recommendations for the future provide direction toward positive change for CIE into the 21st century.